Prebiotic And Enzymatic Indices of Split Gill Mushroom (Schizophyllum Commune) - Sopandi, Tatang; Putri Hanifah, Riza; Ardithasari, Bunga; Andriani, Vivin (Indonesian Journal of Microbiology, 2025)
This study aims to evaluate the prebiotic activity and index as well as the enzymatic activity and index of the split gill mushroom (Schizophyllum commune) through the characterization of the extract and its mycelial part. The extract was prepared through water maceration for 24 hours, then tested for its prebiotic ability against Lactobacillus casei bacteria and its inhibition against Escherichia coli. Inulin was used as a positive control to compare the effectiveness of the extract in supporting the growth of beneficial bacteria and suppressing pathogenic bacteria. The mycelial portion was grown under controlled conditions and tested for amylase, cellulase, and protease activity using fundamental enzymatic techniques commonly used in biochemical research. The results showed that the mushroom extract of split gill was able to significantly increase the growth of L. casei and showed the ability to inhibit the growth of E. coli. As a reflection of supporting the growth of L. casei bacteria and inhibiting E. coli, the prebiotic index of split gill mushroom extract in this study was higher than inulin. Analysis of the split gill mushroom mycelium confirmed the presence of amylase, cellulase, and protease activities with consistent and reproducible values, although the activities were still lower than those of the commercial enzymes used as a comparison in this study. These findings indicate that the bioactive components of split gill mushrooms have relevant capacity for microbial-based applications. The bioactivity profile obtained from this study strengthens the potential of split gill mushrooms as a source of natural prebiotic compounds and as a producer of multifunctional enzymes that can be utilized in various food biotechnology processes. These results open opportunities for the development of innovative formulations that not only support the growth of probiotic bacteria but also provide additional enzymatic activity to improve bioconversion efficiency in various industrial applications.